2006
DOI: 10.1079/bjn20061746
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of extractives from leaves of Morus alba on human and rat small intestinal disaccharidase activity

Abstract: The inhibitory effect on human and rat intestinal disaccharidase by the extractive from the leaves of Morus alba (ELM) containing 0·24 % 1-deoxynojirimycin equivalent and its inhibitory activities were investigated by the modified Dahlqvist method. In the presence of 1000-fold diluted ELM solution, the sucrase activity of four human samples was inhibited by 96 % and that of maltase and isomaltase by 95 and 99 %, respectively. The activities of trehalase and lactase were inhibited by 44 and 38 %, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 19 publications
(18 reference statements)
2
89
0
4
Order By: Relevance
“…They are widely used in processed foods that have been developed to prevent lifestyle-related diseases. The leaf extract of Morus alba (LEM) also has a suppressive effect on postprandial glucose [1][2][3]. However, the interactions between LEM and prescribed medicines, and the resulting effects on postprandial glucose and insulin, have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are widely used in processed foods that have been developed to prevent lifestyle-related diseases. The leaf extract of Morus alba (LEM) also has a suppressive effect on postprandial glucose [1][2][3]. However, the interactions between LEM and prescribed medicines, and the resulting effects on postprandial glucose and insulin, have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, the interactions between LEM and prescribed medicines, and the resulting effects on postprandial glucose and insulin, have not yet been investigated. LEM markedly suppressed postprandial glucose and insulin in healthy subjects and normal rats [1][2][3], and Mudra et al reported that mulberry suppressed blood glucose after sucrose administration in diabetic subjects [4]. Furthermore, the appearance of polyuria and the elevation of fasting blood glucose and insulin were delayed by the daily intake of LEM in diabetic mice [5].…”
Section: Introductionmentioning
confidence: 99%
“…D-glucose analogs such as voglibose, miglitol and acarbose, with nitrogen-in-rings, have been used for the treatment of DM (Drent et al, 2002;Raimbaud et al, 1992;Yasuda et al, 2003). We have clarified that ELM competitively inhibits the activity of sucrase, maltase, and isomaltase using human and rat intestinal homogenates, and significantly suppresses the increment in blood glucose levels, when ELM is administered with sucrose to rats (Oku et al, 2006). In addition, we found that confections with ELM effectively suppress the postprandial blood levels of glucose and insulin in healthy humans ).…”
Section: Extractive From the Leaves Of Morus Alba (Elm)mentioning
confidence: 99%
“…The inhibitory effect of ELM and ES on sucrase was very strong. The inhibitory constant (Ki) of ELM and ES for sucrase was 2.1×10 -4 mM and 6.7×10 -4 mM, respectively (Oku et al, 2006 ELM, extractive from the leaves of Morus alba; ES, extractive from Salacia chinensis Reaction mixture [cell solution, 0.5 mL; 2% sucrose (final concentration, 1%) in BHI, 0.8 mL; test substance 0.3 mL] incubated at 20° for 24 h at 37°C. In the blank, distilled water was added instead of sucrose.…”
Section: Potential Of Phytochemicals As Anticariogenic Materialsmentioning
confidence: 99%
“…However, white mulberry was mainly known for its excellent antidiabetic action. The flavonoids contained in the leaves and bark of mulberry, especially quercetin and 1-deoxynojirimycin (DNJ) lower significantly blood glucose levels by inhibiting enzyme activity, such as: α-glucosidases, sucrase and maltase (Oku et al 2006). Literature data reports that alcoholic extract from the bark, administered to diabetic rats for 10 days, decreased glucose levels by 59%, thereby raising insulin levels by 44% compared with the control group (Singab et al 2005).…”
Section: The Potential Of White Mulberrymentioning
confidence: 99%